Improve the Traditional Autoencoder Student Classroom Behavior Recognition Algorithm - Zhang, Man; Wei, Yan (2022 2nd International Conference on Computational Modeling, Simulation and Data Analysis (CMSDA), 2022)
Most of the existing behavior recognition methods are aimed at the dynamic behavior in action. When applied to the static behavior recognition environment in the classroom, it is difficult to achieve the ideal effect and waste computing resources. Therefore, aiming at the specific environment of classroom, the paper firstly describes the model theories of traditional Auto Encoder (AE) and Variational Auto Encoder (VAE). On this basis, the optimized variational autoencoder (AVAE) model structure proposed in this paper for the classroom behavior recognition of students is introduced. By loading the encoder with pre-training weight, the feature extraction results are obtained, and the loss function is optimized to reduce the supervision of the decoder during training, so as to identify the student behavior more efficiently. The AVAE model is compared with the current common deep learning feature extraction classification methods, and the performance advantages of the proposed method are verified by experiments.